2019
DOI: 10.3390/soilsystems3010016
|View full text |Cite
|
Sign up to set email alerts
|

Organic Residues and Ammonium Effects on CO2 Emissions and Soil Quality Indicators in Limed Acid Tropical Soils

Abstract: Aglime (agricultural lime), commonly applied to acid soils to increase the soil pH and productivity, may lead to the release of CO2 into the atmosphere or to carbon (C) sequestration, although the processes involved are not fully understood. As large acreages of arable land are limed annually, exploring soil management practices that reduce aglime-induced CO2 emissions from acid soils while maintaining or improving the soil quality is paramount to mitigating the effects of global climate change. This study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…During the 61 days of incubation, a cumulative increase of C-CO 2 was observed due to the application of increasing doses of biochar and organic compost (Figures 2A and 2B). The observation is in agreement with the results of Sistani, Simmons, Jn-Baptiste and Novak (2019), and Bramble et al (2019).…”
Section: Accumulated Carbon In the C-co 2 Formsupporting
confidence: 93%
See 1 more Smart Citation
“…During the 61 days of incubation, a cumulative increase of C-CO 2 was observed due to the application of increasing doses of biochar and organic compost (Figures 2A and 2B). The observation is in agreement with the results of Sistani, Simmons, Jn-Baptiste and Novak (2019), and Bramble et al (2019).…”
Section: Accumulated Carbon In the C-co 2 Formsupporting
confidence: 93%
“…These results are corroborated by Cross andSohi (2011), andSagrilo, Jeffery, Hoffland andKuyper (2015). The C-CO 2 evolution decreases in soils incubated with biochar (Shen et al, 2017;Bramble, Gouveia, & Ramnarine, 2019), suggesting a low amount of degradable substrate, and access of more recalcitrant by the microbes with time, at lower rates (Andrade, Oliveira, & Cerri, 2006).…”
Section: C-co 2 Evolution Ratementioning
confidence: 56%
“…Acrisol is a common type of soil, distributed mainly in humid tropical/subtropical and even warm temperate regions, such as Southern Asia, South China, and Southeast US [7]. Lime application is one of the most widely applied management practices for amending Acrisol [8]. In addition to lowering soil acidity, lime application could improve soil structure, and thus typically promote agriculture and forest productivities [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the soil microbial community generally shifts from fungi to bacteria as the pH increases after lime application [15]. However, most of these studies focused on the soil microbial communities in agricultural soil [8,16]. We still have a poor understanding of how fungal and bacterial communities respond to lime application in forests, especially for Eucalyptus plantations in South China where soils are strongly acidic.…”
Section: Introductionmentioning
confidence: 99%
“…The use of agricultural lime to improve acidic soils can either lead to increased release of CO 2 in the atmosphere, or to carbon sequestration. For instance, Bramble, Gouveia and Ramnarine [81] found that combining the application of agricultural lime with poultry litter prevented CO 2 emissions. Finally, it is important to also consider energy conservation in climate mitigation strategies.…”
Section: Carbon Sequestrationmentioning
confidence: 99%